Effectiveness of a programme to promote the acquisition of vocabulary in Children - Morales, Francisco Manuel (Revista de Investigación en Logopedia, 2013)
The way vocabulary is taught is not enough structured in schools. Children do not usually process the full meaning of words until later on in schools. This makes it difficult for them to understand and use the appropriate language in all areas of their learning, which involves their educational process as well as their social and school adjustment. In this context, the intervention introduced in this study is intended to facilitate the acquisition of family-related semantic field lexicon that is considered a priority for the development of essential cognitive processes in Preschool Education. To do so, children are required to do more than understand the use of words as mere labels of things, in order to be able to refer to the relationships between objects and other phenomena that makes it easier to intellectually manipulate their reality. The present study aims to determine whether the systematic and sequential intervention that has been carried out - based on the theory of semantic features - benefits the acquisition of lexicon. Participants were 70, 3rd Year, Preschool students. Results show that the intervention to promote the acquisition of vocabulary has been effective.
Keywords: Children; Intervention; Programme; Vocabulary.